Estimativa espacial do rendimento específico e da recarga subterrânea em aquífero sedimentar não confinado localizado na região litorânea do Nordeste do Brasil - Claudino, Cinthia Maria de Abreu (2021)
Knowledge about groundwater recharge is necessary for a better management of such resource but remains a great challenge. One of the most used methods for estimating groundwater recharge is the Water Table Fluctuation (WTF), which requires knowledge of the specific yield (Sy) of the aquifer for its application. Sy is a parameter difficult to obtain due to its high spatial variability. Therefore, this research seeks to quantify the groundwater recharge of a non-confined sedimentary aquifer in part of the coastal region of Northeast Brazil using spatially estimated values of Sy. The water balance method was then applied to estimate the Sy values and the groundwater recharge spatially. These methodologies were applied in the Gramame river basin and the low course of the Paraíba river basin considering groundwater level data obtained from 27 wells for three hydrological years (2015-2018). The following results of the parameters used in the estimates were obtained: average demand of 59,95 mcm, return flow of 0,14 mcm, base flow of 13,55 mcm , and flow input and output considered insignificant based on the resolution degradation method. Thus, it was possible to estimate the global values of Sy and groundwater recharge equal to 0,131 and 180,22 mm, respectively, which corresponds to 12,37% of the precipitation. This research then generates important values of Sy since it considers the spatial variations of this parameter. This information is relevant for the study region and other coastal aquifers with similar geological characteristics, since from this estimate it is possible to obtain groundwater recharge results in order to contribute as more accurate information for sustainable aquifer management.